Visual Outcome and Complications of Anterior Chamber Intraocular Lens Versus Scleral Fixated Intraocular Lens - Sofia Iqbal, Sanaullah Khan, Mushtaq Ahmad, Muhammad Naeem (Pakistan Journal of Ophthalmology, 2018)
Purpose: To compare the visual outcome and complications associated with anterior chamber IOL versus scleral fixated IOL following cataract surgery with poor capsular support. Material and Methods: This interventional comparative study was conducted from April 2010 to December 2011 in the department of Ophthalmology Hayatabad Medical Complex Peshawar. Thirty two eyes were included in the study consisting of twenty eight patients. They were classified into 2 groups; Group I: Where 16 eyes underwent anterior chamber IOLs (ACIOLs) implantation either primary or secondary and Group II: Where 16 eyes underwent scleral fixated IOLs (SFIOLs) implantation either primary or secondary. Patients were followed for one month, 3 months and 6 months. Results: There was no statistically significant difference noted between the two groups after six months. BCVA 6/6 – 6/9 in 25% preoperatively improved to 56.25% in group – I after six months postoperatively while in group-II it improved from 31.25% to 56%. Complications rate was analysed, corneal astigmatism > 1 diopter was noted 31.25% in group – I and 25% in group – II. Hyphaema / vitreous hemorrhage was 18.75%, IOL decentration was 12.50% in group – II, but no case recorded in group – I. Conclusion: BCVA improved in both groups with no significant differences in outcome in complicated cataract extraction with poor capsular support. However higher rate of complications were noted in